2005
DOI: 10.1152/ajpcell.00629.2004
|View full text |Cite
|
Sign up to set email alerts
|

Distinct and sequential upregulation of genes regulating cell growth and cell cycle progression during hepatic ischemia-reperfusion injury

Abstract: Ischemia-reperfusion injury (IRI) in liver and other organs is manifested as an injury phase followed by recovery and resolution. Control of cell growth and proliferation is essential for recovery from the injury. We examined the expression of three related regulators of cell cycle progression in liver IRI: spermidine/spermine N-acetyltransferase (SSAT), p21 (a cyclin-dependent kinase inhibitor), and stathmin. Mice were subjected to hepatic IRI, and liver tissues were harvested at timed intervals. The expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 44 publications
3
56
1
Order By: Relevance
“…We have previously shown that after hepatic I/R, signals for liver recovery/regeneration do not occur until after 24 h of reperfusion (3,22). Accordingly, although no differences were seen in the degree of liver injury as manifested by serum ALT levels and histology after 8 h of reperfusion in this study, TCR-␦ deficiency may have effects on liver recovery and regeneration.…”
Section: Discussioncontrasting
confidence: 55%
“…We have previously shown that after hepatic I/R, signals for liver recovery/regeneration do not occur until after 24 h of reperfusion (3,22). Accordingly, although no differences were seen in the degree of liver injury as manifested by serum ALT levels and histology after 8 h of reperfusion in this study, TCR-␦ deficiency may have effects on liver recovery and regeneration.…”
Section: Discussioncontrasting
confidence: 55%
“…21,22 The microtubule-destabilizing protein stathmin is indeed expressed only in small quantities by resting hepatocytes but is highly expressed by mitotic hepatocytes during regeneration after hepatic ischemia/reperfusion and partial hepatectomy and in hepatocarcinogenesis. 4,23 Therefore, stathmin fulfills all the requirements of a protein whose expression is temporarily induced in hepatocytes of normal liver tissue after stimulation of cell growth but is reduced to a basal level after cessation of stimuli. Although a fast effect on stathmin expression was observed after FBP-1 inhibition (⌬6 hours), no previously described FUSE site was found upstream of the first STMN1 exon (up to Ϫ2,000 bp).…”
Section: Discussionmentioning
confidence: 99%
“…A P value of Ͻ 0.05 was considered statistically significant. 4 -treated mice. The hepatic expression of SSAT, SMO, and ODC transcripts is induced as early as 6 h post-CCl 4 administration (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Although SSAT expression increases in CCl 4 -induced liver injury its role and the contribution of enhanced polyamine catabolism to the pathophysiology of hepatotoxic injuries in general, and CCl 4 -induced liver injury in particular, are not understood (21). Recent studies indicate that ␣-methylspermidine, a stable polyamine mimetic, has an ameliorative effect on CCl 4 -induced liver toxicity, suggesting that polyamines and their catabolism are important mediators of this injury (13). We hypothesize that increased SSAT expression and activity in the hepatocytes of animals treated with CCl 4 contributes to liver injury.…”
mentioning
confidence: 87%
See 1 more Smart Citation